A catalyst for preparing o-cresol and 2,6-dimethylphenol

By using Fe/V/Zr catalyst, the contradiction between phenol conversion rate and o-cresol selectivity in phenol vapor phase methylation reaction in the prior art is solved, and a catalytic effect of high yield and long life is achieved.

CN119733523APending Publication Date: 2025-04-01SHANGHAI ZHONGHUA TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411929053.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, the phenol vapor phase methylation reaction has the problem that o-cresol selectivity is low when the phenol conversion rate is high, and phenol conversion rate is low when the o-cresol selectivity is high, resulting in a low overall yield and a short catalyst life.

Method used

Using Fe/V/Zr catalyst, it is prepared by co-precipitating iron, vanadium and zirconium elements in a specific molar ratio, and is used to catalyze the methylation reaction of phenol and methanol. The molecular formula of this catalyst is FeaVbZrcO, and the valence states of iron, vanadium and zirconium are +3 valence, +5 valence and +4 valence, respectively.

Benefits of technology

While ensuring high phenol conversion, the yields of o-cresol and 2,6-dicresol are improved, and the activity and life of the catalyst are significantly improved. The phenol conversion rate can be maintained above 90%, and the o-cresol selectivity is above 50%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733523A_ABST
    Figure CN119733523A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalysts, and in particular to a catalyst, a preparation method thereof, and a method for preparing o-cresol and 2,6-dimethylphenol using the catalyst. The molar ratio of iron element, vanadium element and zirconium element in the catalyst of the present invention is 100:(2-15):(1-6), and its preparation process is simple, and raw material cost is low. The catalyst of the present invention has the characteristics of high conversion rate, high o-cresol selectivity and high stability in the reaction of phenol methylation to prepare o-cresol and 2,6-dimethylphenol, and the phenol conversion rate can reach more than 90%, the o-cresol selectivity can reach more than 50%, and the catalyst has a single-pass life of more than 4200 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a catalyst, a preparation method thereof and a method for preparing o-cresol and 2,6-dimethylphenol by using the catalyst. Background Art

[0002] The ortho-methylation products of phenol include o-cresol and 2,6-dimethylphenol, both of which are important fine chemical intermediates. o-Cresol is an intermediate for the synthesis of pesticides, medicines, resins, spices, antioxidants and other products. o-Cresol can be used to synthesize o-cresol phenolic resin, o-cresol phenolic epoxy resin, phenoxycarboxylic acid herbicides (MCPA, MCPB, etc.), and can also be used to produce o-hydroxybenzaldehyde, dyes, spices and antioxidants, and the market demand is very large. 2,6-Dimethylphenol is an important monomer for the synthesis of polyphenylene ether heat-resistant resins and an engineering plastics improver. It is also a synthetic raw material for some important pharmaceutical intermediates.

[0003] At present, the main method for synthesizing o-cresol is the gas phase alkylation of phenol and methanol. After the phenol and methanol are gasified, they pass through a catalyst to generate o-cresol, while 2,6-dimethylphenol and a small amount of 2,4,6-trimethylphenol are produced as by-products. General Motors of the United States first used magnesium oxide as a catalyst and achieved industrialization. Later, other companies successively developed Fe 2 O 3 Catalyst, MnO 2 Catalyst, V 2 O 5 Catalyst and Cr 2 O 3 Catalysts, etc. Among them, MnO 2 MgO series catalysts are high temperature catalysts with a reaction temperature of 400℃-500℃ and a short catalyst life; Fe 2 O 3 Series catalyst, Cr 2 O 3 The series of catalysts are medium-temperature type, with the advantages of high activity and low reaction temperature.

[0004] Patent application CN101514144A uses Fe-Mg-Ce catalyst, and the evaluation conditions are phenol: xylenol: methanol: water = 34:10:38:18 (wt%), and the space velocity is 1.2h -1 , and at normal pressure, N 2 As carrier gas, when the reaction temperature is 280-450℃, the catalyst life can reach 500 hours, the average conversion rate of phenol is 33.4%, and the selectivity of o-cresol is 96%. Although the selectivity of o-cresol is high, the conversion rate of phenol is not high, the catalyst activity is low, and xylenol needs to be added to the reactants.

[0005] Patent application CN102824916A uses Fe-Mg-Sb catalyst, and the evaluation conditions are phenol:methanol:water molar ratio = 1:3:1, space velocity 1h -1 , with N 2 As carrier gas, at normal pressure, reaction temperature of 320-350℃, the catalyst life reaches 2000 hours, the average conversion rate of phenol is 44.5%, the selectivity of o-cresol is 90.96%, and the selectivity of xylenol is 8.46%. Although the catalyst life reaches 2000 hours, the catalyst activity is still low.

[0006] From the above analysis, it is found that the gas-phase methylation reaction of phenol has the phenomenon that when the conversion rate is high, the selectivity of o-cresol is low, and when the selectivity of o-cresol is high, the conversion rate of phenol is low. The prior art has the problems of low overall yield of o-cresol and short life. Summary of the invention

[0007] The present invention aims at the above-mentioned problems existing in the prior art, and provides a composite oxide catalyst and a preparation method thereof, as well as a method for preparing o-cresol and 2,6-xylenol using the composite oxide catalyst of the present invention. The present invention can obtain high yields of o-cresol and 2,6-xylenol while ensuring a high phenol conversion rate, and can improve the selectivity of o-cresol (for example, to more than 50%).

[0008] Specifically, one aspect of the present invention provides a Fe / V / Zr catalyst, wherein the Fe / V / Zr catalyst contains iron, vanadium and zirconium, and the molar ratio of the iron, vanadium and zirconium is 100:(2-15):(1-6).

[0009] In one or more embodiments, the Fe / V / Zr catalyst has a molecular formula of Fe a V b Zr c O, where 0<a<1, 0<b<1, 0<c<1, a:b:c=100:(2-15):(1-6), 3a+5b+4c=2.

[0010] In the present invention, the molecular formula Fe can be calculated based on the valence states of Fe, V, Zr and O in the catalyst, which are +3, +5, +4 and -2, respectively, and the molar ratio of the three metal elements Fe, V and Zr. a V b Zr c The values ​​of a, b, and c in O.

[0011] In some embodiments, a is 0.4-0.7, e.g., 0.4, 0.45, 0.5, 0.53, 0.55, 0.57, 0.59, 0.6, 0.62, 0.65, 0.7.

[0012] In some embodiments, b is 0.01-0.07, e.g., 0.01, 0.015, 0.017, 0.02, 0.025, 0.03, 0.034, 0.035, 0.04, 0.045, 0.047, 0.05, 0.055, 0.059, 0.06, 0.065, 0.07.

[0013] In some embodiments, c is 0.005-0.05, for example, 0.005, 0.006, 0.0066, 0.007, 0.008, 0.01, 0.012, 0.014, 0.016, 0.017, 0.018, 0.02, 0.025, 0.029, 0.03, 0.035, 0.04, 0.05.

[0014] Another aspect of the present invention provides a method for preparing the Fe / V / Zr catalyst in any embodiment of the present invention, the method comprising: dissolving an iron source, a vanadium source and a zirconium source in water, adding a precipitant dropwise for co-precipitation, and obtaining the Fe / V / Zr catalyst after post-treatment.

[0015] In one or more embodiments, the molar ratio of the iron element in the iron source to the vanadium element in the vanadium source is 100:(2-15).

[0016] In one or more embodiments, the molar ratio of the iron element in the iron source to the zirconium element in the zirconium source is 100:(1-6).

[0017] In one or more embodiments, the iron source is selected from one or more of ferric nitrate, ferric chloride, and ferric sulfate.

[0018] In one or more embodiments, the vanadium source is selected from one or more of ammonium metavanadate, vanadium oxalate, and ammonium vanadate.

[0019] In one or more embodiments, the zirconium source is selected from one or more of zirconium nitrate, zirconium oxychloride, and zirconium chloride.

[0020] In one or more embodiments, the precipitating agent is aqueous ammonia.

[0021] In one or more embodiments, the post-treatment comprises the following steps:

[0022] The coprecipitate is aged, dried for the first time, and then pulverized. The pulverized product is washed, dried for the second time, and calcined.

[0023] In one or more embodiments, the aging time is 1-5 hours.

[0024] In one or more embodiments, the first drying is carried out at a temperature of 80-150° C. and for a drying time of 6-12 hours.

[0025] In one or more embodiments, the second drying temperature is 80-120° C., and the drying time is 6-12 hours.

[0026] In one or more embodiments, the calcination temperature is 350° C.-600° C., and the calcination time is 2-6 hours.

[0027] Another aspect of the present invention provides a method for preparing o-cresol and 2,6-dimethylphenol, the method comprising: contacting a material containing phenol and methanol with the Fe / V / Zr catalyst described in any embodiment of the present invention or the Fe / V / Zr catalyst prepared by the method described in any embodiment of the present invention, so that phenol undergoes a methylation reaction.

[0028] In one or more embodiments, in the material containing phenol and methanol, the molar ratio of phenol to methanol is 1:(3-5).

[0029] In one or more embodiments, the temperature of the reaction is 300°C to 400°C.

[0030] In one or more embodiments, the reaction space velocity is 0.8-1.2h -1 .

[0031] In one or more embodiments, the reaction pressure is 0.1 MPa-0.5 MPa.

[0032] The catalyst preparation method of the present invention adopts a multi-component coprecipitation method, has a simple preparation method, low raw material cost, and is easy to scale up for mass production. It is applied to the reaction of preparing o-cresol and 2,6-dimethylphenol by methylation of phenol, and has the characteristics of high conversion rate, high o-cresol selectivity and high stability. After the catalyst runs for 4200 hours, the phenol conversion rate can be maintained at more than 90%, and the o-cresol selectivity is more than 50%. The prepared catalyst has high activity and long service life, and can obtain o-cresol products and 2,6-dimethylphenol products with higher yields under the premise of maintaining a high phenol conversion rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the X-ray diffraction (XRD) diagram of Example 3 in the present invention.

[0034] Figure 2 This is the XRD diagram of Example 4 in the present invention.

[0035] Figure 3 This is the XRD diagram of Comparative Example 1 in the present invention.

[0036] Figure 4 It is the XRD diagram of comparative example 2 in the present invention. DETAILED DESCRIPTION

[0037] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this document. Unless otherwise specified, all technical and scientific terms used in this document have the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this specification shall prevail.

[0038] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0039] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0040] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0041] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope defined by the present invention.

[0042] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0043] Herein, o-cresol refers to o-methylphenol; 2,6-dimethylphenol refers to 2,6-dimethylphenol.

[0044] In the Fe / V / Zr catalyst of the present invention, the molar ratio of iron to vanadium is 100:(2-15), for example, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14.

[0045] In the Fe / V / Zr catalyst of the present invention, the molar ratio of iron element to zirconium element is 100:(1-6), for example, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, 100:5, 100:5.5.

[0046] The Fe / V / Zr catalyst of the present invention can be prepared by the following method: dissolving an iron source, a vanadium source and a zirconium source in water, adding a precipitant dropwise for co-precipitation, and obtaining a Fe / V / Zr catalyst after post-treatment; the iron source is preferably one or more of ferric nitrate, ferric chloride or ferric sulfate, the vanadium source is preferably one or more of ammonium metavanadate, vanadium oxalate or ammonium vanadate; the zirconium source is preferably one or more of zirconium nitrate, zirconium oxychloride or zirconium chloride.

[0047] The molar ratio of iron in the iron source to vanadium in the vanadium source can be 100:(2-15), for example 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14.

[0048] The molar ratio of the iron element in the iron source to the zirconium element in the zirconium source can be 100:(1-6), for example, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, 100:5, 100:5.5.

[0049] The post-treatment preferably comprises the following steps: aging the coprecipitate, drying it for the first time, and then pulverizing it; washing the pulverized product, drying it for the second time, and calcining it.

[0050] The aging time is preferably 1-5 hours, for example 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h.

[0051] The temperature of the first drying is preferably 80-150° C., such as 90° C., 100° C., 110° C., 120° C., 130° C., 140° C. The time of the first drying is preferably 6-12 hours, such as 7h, 8h, 9h, 10h, 11h.

[0052] When the coprecipitate is pulverized after the first drying, it is preferred to pulverize the coprecipitate to 60-80 mesh, such as 65 mesh, 70 mesh, or 75 mesh.

[0053] The temperature of the second drying is preferably 80-120° C., such as 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C. The time of the second drying is preferably 6-12 hours, such as 7h, 8h, 9h, 10h, 11h.

[0054] The calcination temperature is preferably 350° C.-600° C., for example 360° C., 370° C., 380° C., 390° C., 400° C., 410° C., 420° C., 430° C., 440° C., 450° C., 460° C., 470° C., 480° C., 490° C., 500° C., 510° C., 520° C., 530° C., 540° C., 550° C., 560° C., 570° C., 580° C., 590° C. The calcination time is preferably 2-6 hours, for example 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h.

[0055] The Fe / V / Zr catalyst of the present invention can be used to prepare o-cresol and 2,6-xylenol in a phenol-methanol gas phase method, and the specific steps are to load the Fe / V / Zr catalyst into a reactor, introduce a mixed gas of phenol and methanol, and react at high temperature. In the process of preparing o-cresol and 2,6-xylenol in a phenol-methanol gas phase method, the reaction products are mainly o-cresol and 2,6-xylenol, and a small amount of by-products such as p-cresol, 2,4,6-trimethylphenol, etc. are generated.

[0056] When the Fe / V / Zr catalyst of the present invention is used to prepare o-cresol and 2,6-dimethylphenol, the molar ratio of phenol to methanol can be 1:(3-5), for example, 1:3.5, 1:4, or 1:4.5.

[0057] When the Fe / V / Zr catalyst of the present invention is used to prepare o-cresol and 2,6-dimethylphenol, the introduction space velocity of phenol and methanol can be 0.8-1.2h -1 , for example 0.9h -1 , 1h -1 , 1.1h -1 .

[0058] When the Fe / V / Zr catalyst of the present invention is used to prepare o-cresol and 2,6-dimethylphenol, the reaction temperature is preferably 300°C-400°C, for example, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, more preferably 335°C-380°C.

[0059] When the Fe / V / Zr catalyst of the present invention is used to prepare o-cresol and 2,6-dimethylphenol, the reaction pressure is preferably 0.1 MPa-0.5 MPa, for example, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, 0.35 MPa, 0.4 MPa, 0.45 MPa.

[0060] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0061] In the present invention, the molecular formula of the catalyst is calculated based on the molar ratio of iron, vanadium and zirconium in the raw materials, and the valence states of the iron, vanadium and zirconium in the catalyst are +3, +5 and +4 respectively.

[0062] In the present invention, the calculation formula of the conversion rate of phenol is: phenol conversion rate = molar amount of converted phenol / total molar amount of phenol before reaction × 100%;

[0063] In the present invention, the calculation formula of the selectivity of o-cresol is: o-cresol selectivity = molar amount of o-cresol generated by the reaction / molar amount of phenol converted × 100%;

[0064] In the present invention, the calculation formula of the selectivity of 2,6-xylenol is: 2,6-xylenol selectivity = molar amount of 2,6-xylenol generated by the reaction / molar amount of phenol converted × 100%.

[0065] Example 1

[0066] 121.20 g of ferric nitrate nonahydrate, 0.98 g of ammonium metavanadate and 3.60 g of zirconium nitrate pentahydrate were dissolved in 1000 g of deionized water at 70°C. After the dissolution was complete, 90 g of ammonia water was added dropwise until the precipitation was complete. After aging at room temperature for 2 hours, the mixture was filtered and dried at 80°C for 12 hours. After drying, the mixture was crushed and washed until the conductivity was less than 100 μS / m. The mixture was dried at 120°C for 6 hours and calcined at 400°C for 6 hours to obtain a product with the molecular formula of Fe 0.62 V 0.017 Zr 0.017 Fe / V / Zr catalyst for O.

[0067] Example 2

[0068] 121.20 g of ferric nitrate nonahydrate, 1.97 g of ammonium metavanadate and 1.42 g of zirconium nitrate pentahydrate were dissolved in 1000 g of deionized water at 70°C. After the dissolution was complete, 90 g of ammonia water was added dropwise until complete precipitation. After aging at room temperature for 5 hours, the mixture was filtered and dried at 100°C for 12 hours. After drying, the mixture was crushed and washed until the conductivity was less than 100 μS / m. The mixture was dried at 120°C for 6 hours and calcined at 490°C for 2 hours to obtain a product with the molecular formula of Fe 0.62 V 0.034 Zr 0.0066 Fe / V / Zr catalyst for O.

[0069] Example 3

[0070] 121.20 g of ferric nitrate nonahydrate, 1.97 g of ammonium metavanadate and 3.60 g of zirconium nitrate pentahydrate were dissolved in 1000 g of deionized water at 70°C. After the dissolution was complete, 90 g of ammonia water was added dropwise until complete precipitation. After aging at room temperature for 3 hours, the mixture was filtered and dried at 100°C for 12 hours. After drying, the mixture was crushed and washed until the conductivity was less than 100 μS / m. The mixture was dried at 120°C for 6 hours and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.59 V 0.034 Zr 0.017 O of Fe / V / Zr catalyst. The XRD pattern of the catalyst is shown in Figure 1 shown.

[0071] Example 4

[0072] 121.20 g of ferric nitrate nonahydrate, 2.91 g of ammonium metavanadate and 3.60 g of zirconium nitrate pentahydrate were dissolved in 1000 g of deionized water at 70°C. After the dissolution was complete, 90 g of ammonia water was added dropwise until complete precipitation. After aging at room temperature for 4 hours, the mixture was filtered and dried at 100°C for 6 hours. After drying, the mixture was crushed and washed until the conductivity was less than 100 μS / m. The mixture was dried at 120°C for 6 hours and calcined at 430°C for 4 hours to obtain a product with the molecular formula of Fe 0.57 V 0.047 Zr 0.016 O of Fe / V / Zr catalyst. The XRD pattern of the catalyst is shown in Figure 2 shown.

[0073] Example 5

[0074] 121.20g of ferric nitrate nonahydrate, 3.90g of ammonium metavanadate and 7.20g of zirconium nitrate pentahydrate were dissolved in 1000g of deionized water at 70°C, and 90g of ammonia water was added dropwise after the dissolution was complete until complete precipitation. After aging at room temperature for 5 hours, the mixture was filtered, dried at 100°C for 12 hours, crushed after drying, washed until the conductivity was less than 100μS / m, dried at 120°C for 12 hours, and calcined at 420°C for 5 hours to obtain a product with the molecular formula of Fe 0.53V 0.059 Zr 0.029 Fe / V / Zr catalyst for O.

[0075] Example 6

[0076] 121.20 g of ferric nitrate nonahydrate, 3.90 g of ammonium metavanadate and 7.21 g of zirconium nitrate pentahydrate were dissolved in 1000 g of deionized water at 70°C. After the dissolution was complete, 90 g of ammonia water was added dropwise until complete precipitation. After aging at room temperature for 5 hours, the mixture was filtered and dried at 100°C for 12 hours. After drying, the mixture was crushed and washed until the conductivity was less than 100 μS / m. The mixture was dried at 120°C for 12 hours and calcined at 500°C for 1 hour to obtain a product with the molecular formula of Fe 0.53 V 0.059 Zr 0.029 Fe / V / Zr catalyst for O.

[0077] Comparative Example 1

[0078] 12.12 g of ferric nitrate nonahydrate and 3.51 g of ammonium metavanadate were dissolved in 150 g of methanol, 18.45 g of zirconium oxide powder was added to the above solution, the reaction system was heated to 70°C, and the mixture was evaporated while stirring until there was no water, dried at 120°C for 12 hours, and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.07 V 0.07 Zr 0.36 O catalyst. The XRD pattern of the catalyst is as follows Figure 3 shown.

[0079] Comparative Example 2

[0080] 12.12g of ferric nitrate nonahydrate, 3.51g of ammonium metavanadate and 64.40g of zirconium nitrate pentahydrate were dissolved in 1000g of deionized water at 70°C, and 40g of ammonia water was added dropwise after the dissolution was complete until complete precipitation. After aging at room temperature for 3 hours, the mixture was filtered, dried at 120°C for 12 hours, crushed after drying, washed until the conductivity was less than 100μS / m, dried at 120°C for 12 hours, and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.07 V 0.07 Zr 0.36 O catalyst. The XRD pattern of the catalyst is as follows Figure 4 shown.

[0081] Comparative Example 3

[0082] 121.20 g of ferric nitrate nonahydrate and 1.97 g of ammonium metavanadate were dissolved in 1000 g of deionized water at 70°C. After the dissolution was complete, 90 g of ammonia water was added dropwise until complete precipitation. After aging at room temperature for 3 hours, the mixture was filtered and dried at 120°C for 12 hours. After drying, the mixture was crushed and washed until the conductivity was less than 100 μS / m. The mixture was dried at 120°C for 12 hours and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.61 V 0.034 O catalyst.

[0083] Comparative Example 4

[0084] 121.20 g of ferric nitrate nonahydrate, 5.86 g of ammonium metavanadate and 0.77 g of zirconium nitrate pentahydrate were dissolved in 1000 g of deionized water at 70°C, and 90 g of ammonia water was added dropwise after the dissolution was complete until the precipitation was complete. After aging at room temperature for 3 hours, the mixture was filtered, dried at 120°C for 12 hours, crushed after drying, washed until the conductivity was less than 100 μS / m, dried at 120°C for 12 hours, and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.52 V 0.087 Zr 0.0031 O catalyst.

[0085] Comparative Example 5

[0086] 121.20 g of ferric nitrate nonahydrate, 0.39 g of ammonium metavanadate and 11.45 g of zirconium nitrate pentahydrate were dissolved in 1000 g of deionized water at 70°C, and 90 g of ammonia water was added dropwise after the dissolution was complete until the precipitation was complete. After aging at room temperature for 3 hours, the mixture was filtered, dried at 120°C for 12 hours, crushed after drying, washed until the conductivity was less than 100 μS / m, dried at 120°C for 12 hours, and calcined at 450°C for 3 hours to obtain a product with the molecular formula of Fe 0.59 V 0.0064 Zr 0.052 O catalyst.

[0087] Test Case

[0088] 1. Performance evaluation experiment of catalyst in o-cresol synthesis

[0089] In the following experiments, the reaction time (TOS time) of the catalyst and the raw material in the reactor was 200 h. The catalyst was sieved to obtain particles with a mesh size of 12-20 and then filled into the reactor.

[0090] Experimental condition 1:

[0091] O-cresol was prepared from phenol and methanol by a gas phase method. The reaction was carried out in a fixed bed reactor with an inner diameter of φ=13 mm. 5 g of catalysts of 12-20 mesh prepared by Comparative Examples 1-5, Example 1, Example 3-5, and Example 6 were respectively filled in, so that the catalyst bed was located in the constant temperature section of the heating furnace. The reactor was heated to 350°C, phenol and methanol were prepared into a reaction liquid in a molar ratio of 1:5, and a metering pump was used to pass the reaction liquid into the preheater for gasification and then into the reactor. The reaction pressure was set to 0.2 MPa and the reaction space velocity was 1.2 h -1 After 200 hours of reaction, the product was cooled and collected for off-line gas chromatography analysis. The corresponding phenol conversion rate, o-cresol selectivity and 2,6-dimethylphenol selectivity data are shown in Table 1.

[0092] Experimental condition 2:

[0093] O-cresol was prepared from phenol and methanol by a gas phase method. The reaction was carried out in a fixed bed reactor. The inner diameter of the reactor was φ=13 mm. 5 g of the 12-20 mesh catalyst prepared by Example 2, Example 5, and Example 6 were respectively filled in, and the catalyst bed was located in the constant temperature section of the heating furnace. The reactor was heated to 380°C, phenol and methanol were prepared into a reaction liquid in a molar ratio of 1:3, and a metering pump was used to pass the preheater to gasify and then pass it into the reactor. The reaction pressure was set to 0.2 MPa and the reaction space velocity was 0.8 h -1 After 200 hours of reaction, the product was cooled and collected for off-line gas chromatography analysis. The corresponding phenol conversion rate, o-cresol selectivity and 2,6-dimethylphenol selectivity data are shown in Table 1.

[0094] Table 1: Performance of catalysts in o-cresol synthesis at TOS = 200h

[0095]

[0096]

[0097] It can be seen from Table 1 that the reaction of preparing o-cresol using the Fe / V / Zr catalyst of the present invention has a high phenol conversion rate and a high o-cresol selectivity. When the phenol conversion rate exceeds 90%, the o-cresol selectivity can reach more than 50%.

[0098] It can be seen from the experimental results of Examples 1-5 and Comparative Examples 1-2 that when the content of vanadium and zirconium in the catalyst is too high, so that the molar ratio of iron, vanadium and zirconium does not meet 100:(2-15):(1-6), the phenol conversion rate and o-cresol selectivity of the reaction are poor.

[0099] It can be seen from the experimental results of Examples 1-5 and Comparative Example 3 that when the catalyst does not contain zirconium, the phenol conversion rate and o-cresol selectivity of the reaction are poor.

[0100] It can be seen from the experimental results of Examples 1-5 and Comparative Example 4 that when the vanadium content in the catalyst is too high, so that the molar ratio of iron, vanadium and zirconium does not meet 100:(2-15):(1-6), the phenol conversion rate and o-cresol selectivity of the reaction are poor.

[0101] It can be seen from the experimental results of Examples 1-5 and Comparative Example 5 that when the content of vanadium and zirconium in the catalyst is too low, so that the molar ratio of iron, vanadium and zirconium does not meet 100:(2-15):(1-6), the phenol conversion rate and o-cresol selectivity of the reaction are poor.

[0102] In summary, only when the catalyst contains iron, vanadium and zirconium, and the molar ratio of iron, vanadium and zirconium satisfies 100:(2-15):(1-6), can a good phenol conversion rate and o-cresol selectivity be obtained.

[0103] 2. Long-term performance evaluation experiment of catalyst in o-cresol synthesis

[0104] O-cresol was prepared from phenol and methanol by a gas phase method. The reaction was carried out in a fixed bed reactor with an inner diameter of φ=13 mm. The catalyst prepared in Example 3 was sieved to obtain particles of 12-20 mesh, which were then filled into the reactor so that the catalyst bed was located in the constant temperature section of the heating furnace. The reactor was heated to 350°C, phenol and methanol were mixed into a reaction liquid in a molar ratio of 1:5, and a metering pump was used to pass the liquid into the preheater for gasification and then into the reactor. The reaction pressure was set to 0.2 MPa and the reaction space velocity was 1.2 h -1 After being contacted with the Fe / V / Zr catalyst for 200h, 1000h, 2000h, 3000h and 4200h, the products were cooled and collected for off-line gas chromatography analysis. The corresponding phenol conversion rate, o-cresol selectivity and 2,6-dimethylphenol selectivity data are shown in Table 2.

[0105] Table 2: Performance of catalysts at different TOS times in o-cresol synthesis

[0106]

[0107] It can be seen from Table 2 that the life of the Fe / V / Zr catalyst of the present invention is as long as 4200 hours, and the selectivity of o-cresol reaches more than 50% while maintaining a high phenol conversion rate (greater than 90%).

Claims

1. A Fe / V / Zr catalyst, characterized in that: The Fe / V / Zr catalyst contains iron, vanadium and zirconium, and the molar ratio of the iron, vanadium and zirconium is 100:(2-15):(1-6).

2. The Fe / V / Zr catalyst according to claim 1, characterized in that The molecular formula of the Fe / V / Zr catalyst is Fe a V b Zr c O, where a:b:c=100:(2-15):(1-6).

3. A method for preparing the Fe / V / Zr catalyst according to claim 1 or 2, characterized in that: The method comprises: dissolving an iron source, a vanadium source and a zirconium source in water, dropping a precipitant for co-precipitation, and obtaining a Fe / V / Zr catalyst after post-treatment.

4. The method according to claim 3, characterized in that The method has one or more of the following features: The molar ratio of the iron element in the iron source to the vanadium element in the vanadium source is 100:(2-15); The molar ratio of the iron element in the iron source to the zirconium element in the zirconium source is 100:(1-6); The iron source is selected from one or more of ferric nitrate, ferric chloride and ferric sulfate; The vanadium source is selected from one or more of ammonium metavanadate, vanadium oxalate and ammonium vanadate; The zirconium source is selected from one or more of zirconium nitrate, zirconium oxychloride and zirconium chloride; The precipitant is aqueous ammonia.

5. The method according to claim 3, characterized in that The post-processing comprises the following steps: The coprecipitate is aged, dried for the first time, and then pulverized. The pulverized product is washed, dried for the second time, and calcined.

6. The method according to claim 5, characterized in that The method has one or more of the following characteristics: The aging time is 1-5 hours; The first drying temperature is 80-150°C and the drying time is 6-12 hours; The second drying temperature is 80-120°C and the drying time is 6-12 hours; The calcination temperature is 350° C.-600° C., and the calcination time is 2-6 hours.

7. A method for preparing o-cresol and 2,6-dimethylphenol, characterized in that: The method comprises: contacting a material containing phenol and methanol with the Fe / V / Zr catalyst according to claim 1 or 2 or the Fe / V / Zr catalyst prepared by the method according to any one of claims 3 to 6, so that phenol undergoes a methylation reaction.

8. The method according to claim 7, characterized in that The method has one or more of the following features: In the material containing phenol and methanol, the molar ratio of phenol to methanol is 1:(3-5); The reaction temperature is 300°C-400°C; The reaction space velocity is 0.8-1.2h -1 ; The reaction pressure is 0.1 MPa-0.5 MPa.

Citation Information

Patent Citations

  • Method for preparing o-cresol

    CN101514144A

  • Phenol o-methylated catalyst and its preparation method

    CN102824916A